2021
DOI: 10.1167/iovs.62.15.12
|View full text |Cite
|
Sign up to set email alerts
|

SSBP1-Disease Update: Expanding the Genetic and Clinical Spectrum, Reporting Variable Penetrance and Confirming Recessive Inheritance

Abstract: Purpose To report novel genotypes and expand the phenotype spectrum of SSBP1 -disease and explore potential disease mechanism. Methods Five families with previously unsolved optic atrophy and retinal dystrophy underwent whole genome sequencing as part of the National Institute for Health Research BioResource Rare-Diseases and the UK's 100,000 Genomes Project. In silico analysis and protein modelling was performed on the identified variants. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Most of the therapeutic attempts have focused on LHON, although several years ago it was proposed, and proven in cells to be effective, the use of a recombinant, mitochondrion-targeted restriction enzyme SmaI, which recognizes the GGGCCC motif formed by the m.8993T>G mutation. Once internal to mitochondria, the restriction enzyme destroys mutant mtDNA molecules and promoting the proliferation of wt-mtDNA in NARP/MILS cells shifts the original mutant heteroplasmy under the threshold for OXPHOS dysfunction [ 167 ]. Currently, the preclinical development on the shifting of heteroplasmic mtDNA mutations, including those implicated in NARP and KSS, is ongoing using zinc-finger nucleases (ZFNs), TALEN-based nucleases (TALENs), and more recently meganucleases, all engineered to target mitochondria by an N-terminal mitochondrial targeting sequence (MTS) [ 168 , 169 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Most of the therapeutic attempts have focused on LHON, although several years ago it was proposed, and proven in cells to be effective, the use of a recombinant, mitochondrion-targeted restriction enzyme SmaI, which recognizes the GGGCCC motif formed by the m.8993T>G mutation. Once internal to mitochondria, the restriction enzyme destroys mutant mtDNA molecules and promoting the proliferation of wt-mtDNA in NARP/MILS cells shifts the original mutant heteroplasmy under the threshold for OXPHOS dysfunction [ 167 ]. Currently, the preclinical development on the shifting of heteroplasmic mtDNA mutations, including those implicated in NARP and KSS, is ongoing using zinc-finger nucleases (ZFNs), TALEN-based nucleases (TALENs), and more recently meganucleases, all engineered to target mitochondria by an N-terminal mitochondrial targeting sequence (MTS) [ 168 , 169 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Second, the dominant-negative effect of the mutation can result in variable phenotypes as well. Jurkute et al suggested that mutant SSBP1 functions as a dominant-negative protein interfering with the assembly of functional multimers [ 7 , 24 ]. Thus, the variability of clinical presentations could be associated with the expression levels of the mutant alleles versus the trans alleles.…”
Section: Discussionmentioning
confidence: 99%
“…In some disorders both optic neuropathy and retinopathy coexist: an ACO2 mutation has been linked to optic atrophy, vessel narrowing, and retinal degeneration [52], and patients with pathogenic missense variants in SSBP1 often have optic atrophy, vessel narrowing, and pigmented retinal changes, although there is wide variation [53]. The pigmentary changes may be subtle and the role of comprehensive electrophysiological assessment of retinal function is highlighted; typically, affected individuals show evidence of RGC dysfunction, with additional ffERG abnormalities in some, consistent with a photoreceptor dystrophy (Fig.…”
Section: Optic Neuropathies Associated With Retinopathymentioning
confidence: 99%